Geopolitical Approaches to the Term Study of the “Central Asia” - E. G. Garbuzarova (Проблемы постсоветского пространства)
The article is devoted to the methodological approaches that reveal the essence of the term «Central Asia». After the collapse of the USSR, five Post-Soviet States located in the center of Eurasia, adopted the international name of the region «Central Asia» instead of the soviet term «Central Asia and Kazakhstan». However, at the present stage, the accepted Post-Soviet geopolitical term raises many questions and requires a detailed description. The author analyzes the essence of the term «Central Asia» through the prism of historical, geographical and geopolitical approaches. It is concluded that the historical and geographical borders of the region do not coincide with the borders of the political term «Central Asia». Famous Western and Russian geopolitics are trying to present the region within broader geopolitical boundaries which is due to the geographical features of the region and its hydrocarbon potential. As a result the term “Central Asia” is interpreted differently by researchers.